Development of a Scale to Measure Synergy: A Tool to Evaluate Team-Based Learning in Nursing. Issue 2 (26th March 2021) - Keister, Kathy J.; Farra, Sharon L.; Smith, Sherrill J.; Bottomley, Michael
Abstract: AIM: The purpose of this study was to develop and pilot an instrument to assess group synergy and team-based learning among nursing students. BACKGROUND: Little is known on how to evaluate soft nursing skills such as synergy. METHOD: Nurse faculty were recruited through purposive and snowball sampling to serve on an expert panel. Using the DeVillis framework, three rounds of data were collected using semistructured online surveys. The resulting scale of 34 items was piloted with teams of undergraduate nursing students taking part in a simulation experience. RESULTS: Item-content validity index ranged from .8 to 1.0 for each item. Scale-content validity index average was .93; scale-content validity index universal was .62. Exploratory factor analysis identified three factors. CONCLUSION: This study suggests that synergy is multifactorial and can be assessed by faculty. However, further testing of the scale is needed.